Processamento de nanomateriais em hidrotermal convencional e hidrotermal de microondas - Volanti, Diogo P. [UNESP]; Cavalcante, Laécio S.; Keyson, Dawy; Lima, Renata C. [UNESP]; De Moura, Ana Paula; Moreira, Mario L.; Macário, Leilane R.; Júnior, Mário G. (My University, 2007)
Copper, zinc and nickel oxides present different properties in nanostructured form. These nanomaterials present very interesting morphologies such as urchin and flowers. This differents arquitechures can be employed in near future in several areas of applications as: nanocatalysis, nanooptoeletronic and nanomedicine.
Processing nano materials in conventional hydrothermal and microwave hydrothermal
Keywords: Microwave hydrothermal; Nanocatalysis; Nanooptoeletronics; Hydrothermal synthesis; Medical nanotechnology; Metal oxide ceramics; Microwaves; Morphology; Optoelectronic devices; Nanostructured materials